1993
DOI: 10.2337/diab.42.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor Improves an Impaired Bactericidal Function in Neutrophils From STZ-Induced Diabetic Rats

Abstract: To evaluate whether G-CSF improves an impaired production of oxygen-derived free radicals in diabetic neutrophils, we studied the effect of G-CSF on chemiluminescence amplified by a luciferin analog (CLA-DCL) and luminol (L-DCL) in response to fMLP in neutrophils from STZ-induced diabetic rats. Both CLA-DCL and L-DCL in diabetic neutrophils were significantly reduced, and L-DCL was more sensitive to this inhibition than CLA-DCL. G-CSF did not change the basal chemiluminescence in either control or diabetic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…In this study, both CLA-DCL and L-DCL in response to formylmethonyl-leucyl-phenylalanine were decreased in neutrophils from STZ-induced diabetic rats. These results were consistent with our previous observation that the generation of O 2 Ϫ and a H 2 O 2 -MPO-Cl Ϫ system were reduced in poorly controlled diabetic patients (3, 10) and STZ-induced diabetic rats (4,9). In the present study, cytosolic sorbitol concentration was increased in diabetic neutrophils, which is in agreement with the results of Wilson's group (2, 16).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, both CLA-DCL and L-DCL in response to formylmethonyl-leucyl-phenylalanine were decreased in neutrophils from STZ-induced diabetic rats. These results were consistent with our previous observation that the generation of O 2 Ϫ and a H 2 O 2 -MPO-Cl Ϫ system were reduced in poorly controlled diabetic patients (3, 10) and STZ-induced diabetic rats (4,9). In the present study, cytosolic sorbitol concentration was increased in diabetic neutrophils, which is in agreement with the results of Wilson's group (2, 16).…”
Section: Discussionsupporting
confidence: 83%
“…1): untreated control, epalrestat-treated control, untreated diabetic, and treated diabetic (each group n ϭ 8). Diabetes was induced by a single ip injection of 60 mg/kg BW STZ (Sigma, St. Louis, MO) dissolved in 0.1 m citric buffer (pH 4.2), as described before (9). A rat was considered diabetic if it had a nonfasting serum glucose level more than 20 mmol/liter 3 days after STZ injection.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Sato and Shimizu (17) reported that rhG-CSF improves the production of oxygen-derived free radicals in diabetic neutrophils. This suggests that even in the absence of neutropenia, administration of rhG-CSF may be effective for treating infection in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diabetes may cause immunological deficiencies, including abnormal neutrophil chemotaxis, phagocytosis, and intracellular killing (5-7). These factors help explain reported clinical failure rates for diabetic foot infections of 20 -30% (3,(5)(6)(7). Thus, several investigators have sought adjunctive therapies for treating these potentially severe infections.…”
mentioning
confidence: 99%